2022
DOI: 10.1111/cdev.13779
|View full text |Cite
|
Sign up to set email alerts
|

Antiracism defined as equitable sociocultural interactions in prekindergarten: Classroom racial composition makes a difference

Abstract: students) are projected to represent the majority of public school-age students (National Center for Educational Statistics, 2020), but several studies note that the lived experiences of RMLs are not central to the American schooling system. Instead, many RMLs experience racism. Such racism manifests through school segregation, inequitable school discipline, discontinuities between their home and school culture, disparities in funding between White and non-White school districts, and disparities in academic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…Schools and communities can foster more equitable environments by promoting inclusion among students, particularly those from non‐minoritized backgrounds, to reduce experiences of discrimination. For instance, white parents can engage in ethnic–racial socialization to promote anti‐racism (Hazelbaker et al., 2022), and teachers can engage in anti‐racist pedagogy to promote more equitable learning and student experiences (Curenton et al., 2022). Schools can validate students' experiences and send messages promoting diversity rather than colorblind messages.…”
Section: Discussionmentioning
confidence: 99%
“…Schools and communities can foster more equitable environments by promoting inclusion among students, particularly those from non‐minoritized backgrounds, to reduce experiences of discrimination. For instance, white parents can engage in ethnic–racial socialization to promote anti‐racism (Hazelbaker et al., 2022), and teachers can engage in anti‐racist pedagogy to promote more equitable learning and student experiences (Curenton et al., 2022). Schools can validate students' experiences and send messages promoting diversity rather than colorblind messages.…”
Section: Discussionmentioning
confidence: 99%
“…Contributions to the special section also attended to teacher-facilitated classroom experiences in majority White school contexts that may facilitate the development of anti-racism in pre-K and elementary-aged children. Specifically, Curenton et al (2022) examined how equitable classroom teaching practices in pre-K classrooms (i.e., challenging status quo, equitable discipline, connection to home life) may have influenced racially/ethnically diverse children's academic and social-emotional development. Their findings suggest that equitable teaching practices may foster cognitive and social development among young learners, particularly in more racially and ethnically diverse classrooms, thus speaking to the potential broader positive impact of anti-racist teaching practices for children in diverse classrooms.…”
Section: Col L Ect I V E Con T R I Bu T Ions Of T H E Spec I a L Sect...mentioning
confidence: 99%
“…Leveraging observational methods in early childhood classrooms, Curenton and colleagues (2022) advance scholarship on anti‐racism by seeking to understand the impact of classroom experiences on racially marginalized learners (e.g., African American, Asian American, and Latinx students). Informed by literature on anti‐racist pedagogy (e.g., Kishimoto, 2018) and equitable sociocultural interactions (Curenton et al, 2020), the authors investigated the impact of classroom interactions on children’s academic, behavioral, and developmental outcomes.…”
Section: Overview Of Special Section Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…As race scholars have pointed out, racism definitions shape how anti-racist responses and solutions to racism are framed (Azarmandi, 2022;Lentin, 2004;Müller, 2021). International research within early childhood education has identified the need for racial literacy, anti-racist pedagogies, and critical examinations of power to enhance teachers' understandings (Curenton et al, 2022a(Curenton et al, , 2022bEscayg, 2019). Against the backdrop of the Aotearoa New Zealand Ministry of Education's anti-racism policy direction, this article explores how limited definitions of racism within policy documents in Aotearoa New Zealand result in a limited awareness of exactly how to 'unteach' racism in early childhood education contexts.…”
Section: Introductionmentioning
confidence: 99%